LEADERSHIP AND REVENUE GROWTH OF COMMERCIAL BANKS IN LAGOS STATE, NIGERIA - Amos, N. B., Ariguzo, V. A., Akpa, V. & Odigie, H. (International Journal of Research Science and Management, 2019)
Leadership remains an imperative strategy capable of engendering for growth along revenue lines. The study sought to determine the effect of leadership on revenue growth of selected commercial banks in Lagos state Nigeria. A quantitative survey of 401 managers was conducted using a pre-tested, validated and reliable questionnaire. Findings revealed that leadership positively and significantly affected revenue growth in the three most profitable banks in Lagos State, Nigeria. The study recommends that banks must prioritize leadership as a strategy capable of increasing team member participation, right mind-set and engineering growth of revenue and performance in the long run.